Situation Report: Czechoslovakia, 13 February 1985 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Conjuring Up the Spirit (of the Ghost?) of Yalta High Hurdles between the State and the Church Pacem in Terris Holds Third Federal Congress Discord with Austria over Hydroelectric Project Can Fixed Capital Formation Be Intensified?